2020
DOI: 10.1080/00461520.2020.1730181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sources of scientific evidence and claims in the post-truth era may require reappraising plausibility judgments

Abstract: When individuals have questions about scientific issues, they often search the Internet. Evaluating sources of information and claims they find has become more difficult in the post-truth era. Students are often taught source evaluation techniques, but the proliferation of "fake news" has resulted in a misinformation arms race. As searchers get more sophisticated identifying misleading information, so do purveyors of information who intend to mislead. We draw on a theoretical model of plausibility judgments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 59 publications
2
74
0
6
Order By: Relevance
“…Further, if motivated (e.g., if they are interested and self-efficient), individuals may also reappraise their original judgements, guided by more explicit processing and increased effort in reasoning. In consequence, Sinatra and Lombardi (2020) suggested that fostering individuals' capabilities to quickly make plausibility judgments about information-by efficiently employing their prior beliefs and knowledge-may be more fruitful in "post-truth" contexts (similar to the contexts we previously described for OESI) than training effortful strategies to evaluate information and its sources.…”
Section: (Prior) Attitudes and Beliefsmentioning
confidence: 80%
“…Further, if motivated (e.g., if they are interested and self-efficient), individuals may also reappraise their original judgements, guided by more explicit processing and increased effort in reasoning. In consequence, Sinatra and Lombardi (2020) suggested that fostering individuals' capabilities to quickly make plausibility judgments about information-by efficiently employing their prior beliefs and knowledge-may be more fruitful in "post-truth" contexts (similar to the contexts we previously described for OESI) than training effortful strategies to evaluate information and its sources.…”
Section: (Prior) Attitudes and Beliefsmentioning
confidence: 80%
“…Therefore, it is important to develop critical thinking and decision-making skills on controversial issues. Sinatra and Lombardi (2020) suggested the need to enable students to evaluate the link between information sources and claims, for instance, scientific explanations about complex phenomena. They also argued that explicitly reappraising plausibility judgments may be a critical point in evaluating the relationships between sources of information and knowledge claims.…”
Section: Scientific Arguments About Covid-19mentioning
confidence: 99%
“…However, evaluating claims and sources of information has become more difficult in the post-truth era. Therefore, the post-truth era necessitates a critical evaluation of online information about scientific information (Sinatra and Lombardi 2020). From this perspective, scientific literacy requires not only the critical evaluation of claims, evidence, and sources of information but also the ability to resolve uncertainty in science.…”
Section: Introductionmentioning
confidence: 99%
“…Further, online information sources cover the spectrum in terms of their forms (e.g., websites, blogs, news articles, research articles) and their credibility (Bråten, Strømsø, & Salmerón, 2011; Coiro, 2020; Coiro, Coscarelli, Maykel, & Forzani, 2015). There is also a surprising amount of online content that is either unintentionally misleading or purposefully deceptive, which can make the information search process a precarious undertaking (Sinatra & Lombardi, 2020).…”
Section: Reading Challenges In the Digital Agementioning
confidence: 99%